PROBLEMATIKA PEMBELAJARAN DI MDTA AL-MUTTAQIN KELURAHAN JATI UTOMO KOTA BINJAI - Ade Ayu Angel Liah; Mahariah; Ihsan Satrya Azhar (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
This research is entitled Learning Problems in MDTA Al-Muttaqin, Jati Utomo Village, Binjai City. This research was motivated by teacher performance and inadequate infrastructure in learning at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Al-Muttaqin, Jati Utomo Village, Binjai City. This research uses qualitative phenomenological research methods. This method is intended to develop understanding or explain the meaning of an event experienced by a person or group regarding learning problems at MDTA Al-Muttaqin, Jati Utomo Village, Binjai City. The instruments needed to obtain this data are interviews, observations and documentation. The results of this research include the implementation of learning at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Al-Muttaqin carrying out learning activities in accordance with the learning components, then the problems faced in learning at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Al-Muttaqin, and efforts which will be carried out in overcoming learning problems at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Al-Muttakin, Jati Utomo Village, Binjai City.